A gapless genome assembly of a Japonica variety ‘BD8’ provides insights into rice salt tolerance - Geng, Leiyue; Zou, Tuo; Zhang, Wei; Wang, Shuo; Wang, Haining; He, Guangsheng; Du, Qi (Frontiers in Plant Science, 2025)
BackgroundAccurate genomic information in specific rice varieties is essential for functional gene mining and advancing molecular breeding. Bindao8 (BD8) is an elite Japonica rice variety with notable salt tolerance.ResultsThis study presents a near telomere-to-telomere (T2T) genome assembly of ‘BD8’, with a size of 384.2 Mb and contig N50 of 31.69 Mb. A total of 58,685 genes were identified, 95.93% (56,297) of which were functionally annotated. Phylogenetic analysis clarified the genetic background of this cultivar. Abundant structural variations were detected, and enrichment analysis of unique genes identified four enriched KEGG pathways, including amino sugar and nucleotide sugar metabolism (ko00520), which supplies UDP-glucose/UDP-glucuronate for cell-wall biosynthesis. To address BD8’s salt tolerance, time-course transcriptomic profiling was integrated with the genome, revealing two salt-specific gene clusters (347 and 607 genes) and five significantly enriched salt-responsive KEGG pathways. Notably, the amino sugar and nucleotide sugar metabolism pathway (ko00520) was commonly enriched in both BD8’s unique genes and salt-specific clusters, suggesting that cell-wall precursor supply is a constitutive and inducible component of BD8’s tolerance mechanism.ConclusionThe high-quality BD8 genome assembly will serve as a critical resource for rice functional genomics and genomics-driven molecular breeding. The integration of BD8’s genome with transcriptomic data highlights the amino sugar and nucleotide sugar metabolism pathway as a key target for improving salt tolerance in rice breeding programs.